GOVERNMENT ROLE ANALYSIS: CRYPTOCURRENCIES REVIEW OF THEORY, ISLAMIC LAW AND POLICY IN INDONESIA - Sacipto, Rian; Yasin, Akhmad; Syah, Ardy Firman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The development of an increasingly advanced world, of course, brings a change in the global order model. Under conditions of economic uncertainty both globally and domestically, as well as conditions where exchange rates tend to depreciate, people tend to hedge by purchasing assets that can be traded globally. The phenomenon of cryptocurrencies or what is understood as digital currency and this which is currently rife is becoming one of the activities for the world community. Indonesia is of course also not left behind, the government's action in supporting crypto asset trading is a form of strategy in accelerating, creating, and encouraging efforts to develop Indonesia's digital economy in 2030. In Indonesia, crypto currency has become the government's concern and has become an object regulated in regulation. The bibliographical analysis method in this scientific paper will describe the concept of the results of the analysis and innovations that have great potential for cryptocurrencies. The descriptive analysis provides a comprehensive overview of the research question how to trade cryptocurrencies in the perspective of Islamic law. Another goal is to understand the regulation, especially government policy, from a sharia perspective, the use of virtual currency as a legal payment method is still being debated. In this study, the views of scholars regarding the existence of cryptocurrencies will be conveyed through the interpretation of the perspective of Islamic law and their analysis in relation to the laws and regulations in force in Indonesia